The role of collagen-discoidin domain receptor 1 in HPV-positive and –negative head and neck cancer / Lai Sook Ling - Lai , Sook Ling (2018)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide with oropharyngeal (OPSCC) and oral cavity (OSCC) tumours being the two major subtypes. The five year survival rate of patients with HNSCC has remained around 50% for the past four decades. The global incidence rate of HPV positive OPSCC is on the rise and, for reasons that are currently unclear, patients with HPV-related disease have a better prognosis. Molecular targeted therapies are not in routine use for the treatment of HNSCC and the identification of new therapeutic targets is highly desirable, but this will only be possible with a fuller understanding of the molecular events that drive the disease process. We now know that cancers are comprised of tumour cells and non-malignant cells within the tumour microenvironment (TME). Cancer-associated fibroblasts (CAFs) are predominant within the TME and are known to promote epithelial tumour progression in part via paracrine communication with cancer cells. This study examined the role of the collagen receptor, discoidin domain receptor 1 (DDR1), in the pathogenesis of HNSCC. The results demonstrated that two collagen subtypes, COL8a1 and COL11a1, were expressed by CAFs in vitro and that DDR1 was overexpressed in OPSCC and OSCC tissues. The expression of these proteins was further investigated in OPSCC and OSCC tissues and correlated to socio-demographic and clinico-pathological parameters, including HPV status and patient survival. Multiplex immunohistochemistry was used in conjunction with an automated pathology system to digitally quantify expression, with staining intensities, co-expression of proteins and single cell co-localisation analysed with digital imaging software. In OPSCCs from the United Kingdom, high expression of DDR1 was found to be significantly associated with non-smokers, patients within the moderate and high risk of death groups and lower survival rates. Low expression of COL8a1 in tumours and CAFs was significantly associated with the low risk of death group and regional lymph node metastasis N2, whilst high expression was significantly associated with smoker. In OSCCs from Malaysia, COL8a1 in tumours was significantly associated with small primary tumour depth (1-10mm), bone invasion and deceased outcome. A significant association was found between high expression of COL11a1 in CAFs with traditional risk factors of OSCC, included female gender, Indian ethnicity and betel quid chewing. Collectively, these data show that DDR1 and its ligands are expressed in OPSCCs and OSCCs and high expression levels might negatively influence patient prognosis. Next, the functional role of collagen-DDR1 signalling was examined in vitro using HPV-negative and –positive HNSCC cell lines. Treatment of all cell lines with collagen enhanced cell proliferation, migration and invasion, and made the cells less sensitive to apoptosis induced by Cisplatin. Knockdown of DDR1 with shRNAs confirmed these effects were specific to DDR1. In conclusion, this study demonstrated for the first time that activation of DDR1 on HNSCC cells promotes the malignant phenotype and negatively impacts upon patient prognosis. DDR1 represents a novel therapeutic target for HPV-negative and –positive HNSCC.